Multicriteria evaluation of commercial industrial zone development - Komarovska, Andželika; Ustinovichius, Leonas; Shevchenko, Galina; Nazarko, Lukasz (International Journal of Strategic Property Management, 2015)
The article presents the results of the analysis of Vilnius district commercial-industrial zones. The criteria of analysis are: geographic location, plots and/or groups of plots in the area, operating and planning activities of companies as well as the infrastructure and transport communications development at the engineering level. A theoretical model for investment strategy selection is introduced to identify the possibilities of investment attractiveness. The principle of the investment option with the system of characterizing indicators for development is offered to reflect the lack of cohesion between practical investment promotion and sustainable development of the territories’ indicators. First Publish Online: 1 Apr 2015